2016
DOI: 10.3329/ajmbr.v1i3.26464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spent mushroom compost on yield and fruit quality of tomato

Abstract: An experiment was conducted to observe the performance of the composted spent mushroom substrate (SMS) along with chemical fertilizers on the yield, fruit quality and nutrient uptake by tomato plant for using the mushroom waste through composting. The experiment was laid out in a randomized complete block design with seven replications. Treatments were T 1 : no fertilizer and compost application (control), T 2 : recommended dose of fertilizers (RFD), T 3 : 25% SMC-N+ 75% fertilizer-N, T 4 : RFD + 2.5 t ha -1 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The results are comparable with Ashrafi et al, (2015) [3] who reported that the N, P and K (kg/ha) uptake was increased due to the influences of different treatments of SMC. Gumus and Seker (2017) [9] found that the use of SMC contributed to enhancing the level of organic carbon and nitrogen in the soil.…”
Section: Actinomycetes Populationsupporting
confidence: 90%
“…The results are comparable with Ashrafi et al, (2015) [3] who reported that the N, P and K (kg/ha) uptake was increased due to the influences of different treatments of SMC. Gumus and Seker (2017) [9] found that the use of SMC contributed to enhancing the level of organic carbon and nitrogen in the soil.…”
Section: Actinomycetes Populationsupporting
confidence: 90%
“…e effect of SMS on plant growth and yield was evaluated in comparison to mineral fertilization in baby spinach. Several researches on SMS reveal the influence of SMC from oyster and button mushroom on plant growth yield [43,[58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Tuhy et al (2015) studied the use of spent mushroom substrate (SMS) of Agaricusbisporous as adsobant material for micronutrients to improve yield component of maize plant, he found that grain yield of maize treated with micronutrients delivered with (SMS) was higher than the traditional treatment. Ashrafi et al (2015) established that the application ofSMS compost at a rate of 2.5 t ha -1 along with recommended dose of mineral fertilizer showed the best performance for fruits number, fruit yield, fruit quality (total protein, total sugar, vitamin C, reducing sugar) in addition to nutrient uptake bytomato.…”
Section: Data Presented Inmentioning
confidence: 99%